An Alternative Approach to Solutions of the MGECSC Potential in Presence of External Electric Field - M. K. Bahar (Advances in High Energy Physics)
For the first time the Schrödinger equation with more general exponential cosine screened Coulomb potential in the presence of external electric field is solved approximately and analytically by applying an ansatz to eigenfunction of corresponding Hamiltonian and then energy values and wave functions are obtained. Since this potential turns into four different potential cases when considering different cases of the parameters in the potential, energies and eigenfunctions for these four different potentials are already to be found by solving Schrödinger equation with MGECSC potential. Energy values and wave functions obtained by using different values of potential parameters for each of these four different potential are compared with the results of other studies. Since the obtained general solutions in this study have been found in the presence of external electric field, the external electric field effects on systems with the mentioned four different potentials are also easily investigated. One of advantages of the present results and method is that if external electric field is equal to zero, general mathematical structure of corresponding equations does not change and then electric field effect can be eliminated. The presence or absence of electric field does not prevent solving the Schrödinger equation analytically.